Implementation of Kurikulum Merdeka in creating a more effective learning environment - Dede Supriatna; Laksmi Dewi; Rusman Rusman (Inovasi Kurikulum, 2026)
Improving the quality of education by implementing the Kurikulum Merdeka to create an effective learning environment is crucial. This curriculum is designed to address the challenges of 21st-century learning through a flexible, student-centered approach. This study aims to analyze the effectiveness of the Kurikulum Merdeka implementation in creating an effective learning environment at Labschool Kebayoran Junior High School. The method used was a mixed-methods convergent parallel design that integrated quantitative and qualitative data. Data were collected through student questionnaires and teacher interviews. Quantitative data were analyzed descriptively, while qualitative data were analyzed using the Miles and Huberman model. The results showed that most students assessed the implementation of the Kurikulum Merdeka as effective in creating a conducive learning environment and increasing activity and comfort during the learning process. However, obstacles persisted, including student confusion during the curriculum transition period and suboptimal mastery of the material by some teachers. In conclusion, the Kurikulum Merdeka is considered effective in improving the quality of the learning environment, though it requires greater teacher preparedness and ongoing student mentoring.   Abstrak Peningkatan kualitas pendidikan melalui implementasi Kurikulum Merdeka dalam menciptakan lingkungan belajar yang efektif sangat penting untuk dilakukan. Kurikulum ini dirancang untuk menjawab tantangan pembelajaran abad ke-21 dengan pendekatan yang fleksibel dan berpusat pada murid. Penelitian ini bertujuan untuk menganalisis efektivitas implementasi Kurikulum Merdeka dalam menciptakan lingkungan belajar yang efektif di SMP Labschool Kebayoran. Metode yang digunakan adalah mixed method dengan desain convergent parallel yang mengintegrasikan data kuantitatif dan kualitatif. Data dikumpulkan melalui angket kepada murid serta wawancara dengan guru. Data kuantitatif dianalisis secara deskriptif, sedangkan data kualitatif dianalisis menggunakan model Miles dan Huberman. Hasil penelitian menunjukkan bahwa sebagian besar murid menilai implementasi Kurikulum Merdeka mampu menciptakan lingkungan belajar yang efektif serta meningkatkan keaktifan dan kenyamanan dalam proses pembelajaran. Meskipun demikian, masih ditemukan kendala berupa kebingungan murid selama masa transisi kurikulum dan belum optimalnya penguasaan materi oleh sebagian guru. Kesimpulannya, Kurikulum Merdeka dinilai efektif dalam meningkatkan kualitas lingkungan belajar, meskipun memerlukan peningkatan kesiapan guru serta pendampingan berkelanjutan bagi murid. Kata Kunci: efektivitas pembelajaran; implementasi Kurikulum Merdeka; lingkungan belajar